Watchful waiting? Portuguese approach to otitis media with effusion - Vera-Cruz, Paulo (2021)
Vera-Cruz, P., Larroudé, A., Gouveia, N., Mendes, J., & Coelho, P. S. (2021). Watchful waiting? Portuguese approach to otitis media with effusion. Nascer e Crescer: Birth and Growth Medical Journal, 30(1), 143-151. https://doi.org/10.25753/BirthGrowthMJ.v30.i3.19192